DISKURSUS KEDAULATAN ALLAH DALAM KONTEKS PENDERITAAN AYUB DAN IMPLEMENTASINYA BAGI ORANG PERCAYA - Refamati Gulo; Malik, Malik; Paparang, Stenly Reinal (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
The discourse on the sovereignty of God is always a profound topic in Christian theology. It demonstrates that God's sovereignty shows supreme authority and power over all creation, including human life. In the Book of Job, there are two theological views: first, the orthodox retributive theology view where God is depicted as a figure who acts in relation to human actions, that suffering can occur because humans oppose God. Second, is the theodicy theological view, a belief that God has ordained everything so that human efforts and actions do not make a difference or impact in the history of life. The contradictory modern view sees that God allows suffering because of sin and actions, not as a purity of faith to be closer to God. This research aims to provide a deeper theological understanding of God's sovereignty and its relationship to the suffering of believers. Thus helping believers strengthen their faith in the midst of suffering. This research uses a qualitative method with a theological-hermeneutical analysis approach. As a result, this research can be a source of valuable inspiration and teaching and help believers understand and respond to suffering in light of sovereignty. God's sovereignty affirms that God's sovereignty encompasses His power and authority over all creation, including the suffering experienced by humans. Job is a concrete example of fortitude and faith in the midst of suffering.